The associations of depression, anxiety, and insomnia at baseline with disability at a five-year follow-up point among outpatients with chronic low back pain: a prospective cohort study - Le-Yung Wang; Tsai-Sheng Fu; Mei-Chu Tsia; Ching-I Hung (BMC Musculoskeletal Disorders, 2023)
Abstract Background No previous study has investigated the associations of depression, anxiety, and insomnia at baseline with disability at a five-year follow-up point among outpatients with chronic low back pain (CLBP). The study aimed to simultaneously compare the associations of depression, anxiety, and sleep quality at baseline with disability at a 5-year follow-up point among patients with CLBP. Methods Two-hundred and twenty-five subjects with CLBP were enrolled at baseline, and 111 subjects participated at the five-year follow-up point. At follow-up, the Oswestry Disability Index (ODI) and total months of disability (TMOD) over the past five years were used as the indices of disability. The depression (HADS-D) and anxiety (HADS-A) subscales of the Hospital Anxiety and Depression Scale and the Insomnia Severity Index (ISI) were used to assess depression, anxiety, and insomnia at baseline and follow-up. Multiple linear regression was employed to test the associations. Results The scores of the HADS-D, HADS-A, and ISI were correlated with the ODI at the same time points (both at baseline and follow-up). A greater severity on the HADS-D, an older age, and associated leg symptoms at baseline were independently associated with a greater ODI at follow-up. A greater severity on the HADS-A and fewer educational years at baseline were independently associated with a longer TMOD. The associations of the HADS-D and HADS-A at baseline with disability at follow-up were greater than that of the ISI at baseline, based on the regression models. Conclusion Greater severities of depression and anxiety at baseline were significantly associated with greater disability at the five-year follow-up point. The associations of depression and anxiety at baseline with disability at the long-term follow-up point might be greater than that of insomnia at baseline.